Longitudinal Profiles of Psychological Well-Being and Health: Findings From Japan - Yoo, Jiah; Ryff, Carol D. (Frontiers in Psychology, 2019)
Studies have reported relationships between psychological well-being and physical health in Western cultural contexts. However, longitudinal associations between well-being and health have not been examined in other cultures where different values and beliefs about well-being exist. This paper examined whether longitudinal profiles of well-being predict prospective health among Japanese adults. Data came from 654 people who completed two waves of the Midlife in Japan (MIDJA) Study collected 4–5 years apart. Health outcomes were assessed with subjective health, chronic conditions, physical symptoms, and functional health. The results showed that persistently high well-being predicted better health over time. High-arousal positive affect, which is relatively less valued in Japanese culture, was also associated with better health. The findings add cross-cultural evidence to the cross-time link between well-being and health.